EFFECT OF AN EXERCISE REGIMEN ON BLOOD PRESSURE IN GRADE 1 HYPERTENSIVE ADULTS - Boit, Dr. Edwin Kiptolo; Ogweno, Gordon; Theuri, Dr. Gitahi (Global Journal of Health Sciences, 2020)
Purpose: The primary aim of the study was to assess the change in resting Blood Pressure (BP) following a 6 week exercise regimen in grade 1 hypertensive adults. The Secondary aim of the study was to assess the change in Resting Heart Rate (RHR) after a 6 week exercise regimen in grade I hypertensive adults. Methodology: This study employed an experimental research design because specific conditions were controlled and its effects observed. In this case, exercise was controlled by the researcher and the influences on resting BP and Resting Heart Rate (RHR) observed. A sample of 15 adults was used in this study. Data was analyzed using SPSS version 25 (IBM Limited, UK, 2017) and Microsoft Excel 2013 for Windows. The significance level was set at p<0.05. Data was tested for normal distribution using the Shapiro-Wilk test while the Levenes test was used to test for data normality. Data was determined to be parametric. A paired t-test was used to compare mean differences from baseline, mid-point and post-test within the group Results: There was no significant difference observed at baseline for mean Systolic Blood Pressure (SBP) and Diastolic Blood Pressure (DBP) within the Exercise Group (EX) group (p>0.05). The EX group had a mean SBP and DBP of 142.3 ± 7.4 mmHg and 90.9 ± 3.9 mmHg at baseline. Following an exercise regimen conducted for 45 minutes 5 times a week the SBP and DBP reduced by -2.1 ± 4.2 mmHg and -1.1 ± 4.8 mmHg respectively after 3 weeks and reduced further by -4.6 ± 3.1 mmHg and -3.4 ± 3.9 mmHg after 6 weeks. These changes were not statistically significant (p>0.05) after 3 weeks for SBP and DBP respectively, however they were significant after 6 weeks for both SBP (p<0.001) and DBP (p<0.05). In addition, there was no significant difference observed at baseline for RHR within the EX group (p>0.05). The EX group had a RHR of 76.9 ± 12.6 bpm at baseline. Following an exercise regimen conducted for 45 minutes 5 times a week the RHR reduced by -3.9 ± 4.9 bpm after 3 weeks and reduced further by -6.9 ± 4.9 bpm after 6 weeks. The changes were statistically significant (p<0.05) after 3 weeks and 6 weeks respectively. Recommendations for further research: Since there is limited and conflicting research on the effects of combined aerobic and resistance training (concurrent training) on BP, future research needs to focus on determining whether it is superior to aerobic or resistance training. Future studies on hypertensive individuals could investigate safe methods of increasing exercise intensities in view of the fact that increased exercise intensities have been shown to increase the amount BP reduction. However individuals with hypertension are restricted to lower intensities.